Air quality over Portugal in 2020 - Monteiro, Alexandra (2015)
This works intends to evaluate the impacts of the national emission ceilings (NEC) reduction scenarios on the air quality in Portugal, verifying the fulfillment of the air quality thresholds for 2020. The air quality numerical modeling system WRF–EURAD was applied to this 2020 future scenario and results were compared to the present situation -year 2012. This modeling system was already evaluated for Portugal domain in previous studies, by comparison with measured air quality data, and showed reasonable skills for all the pollutants. This system was applied over the Continental domain of Portugal, using nesting approach, with a horizontal resolution of 5x5 km2, for both scenarios conditions (2012 and 2020) considering the respective emissions data and assuming the 2012 meteorological conditions. The results point towards an improvement of the air quality over Continental Portugal, in particular for particulate matter (in the urban areas of Lisbon and Porto) and SO2 (near specific industrial sources) but do not solve the non–compliance status regarding the O3 threshold value for protection of human health. These results strengthen the importance of including the NEC emission scenarios in the air quality national strategy, but additional mitigation actions need to be designed, with focus on ozone and its precursors, at local and regional scale.